2013
DOI: 10.1136/thoraxjnl-2012-202285
|View full text |Cite
|
Sign up to set email alerts
|

Do fast foods cause asthma, rhinoconjunctivitis and eczema? Global findings from the International Study of Asthma and Allergies in Childhood (ISAAC) Phase Three

Abstract: Background Certain foods may increase or decrease the risk of developing asthma, rhinoconjunctivitis and eczema. We explored the impact of the intake of types of food on these diseases in Phase Three of the International Study of Asthma and Allergies in Childhood. Methods Written questionnaires on the symptom prevalence of asthma, rhinoconjunctivitis and eczema and types and frequency of food intake over the past 12 months were completed by 13-14-year-old adolescents and by the parents/guardians of 6-7-yearold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
181
6
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(207 citation statements)
references
References 39 publications
13
181
6
7
Order By: Relevance
“…Fast food consumption ≥3 times per week was a risk factor for severe asthma in two populations, with OR (95% CI) of 1.39 (1.30-1.49) and 1.27 (1.13-1.42), respectively. However, some inconsistent findings were observed between two populations, and there was also heterogeneity of findings across different study centers and countries [13]. In the present study, fruit consumption ≥3 times a week appeared to be a protective factor against persistent asthma, with an OR of 0.85 (95% CI 0.48-1.50), although the result was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Fast food consumption ≥3 times per week was a risk factor for severe asthma in two populations, with OR (95% CI) of 1.39 (1.30-1.49) and 1.27 (1.13-1.42), respectively. However, some inconsistent findings were observed between two populations, and there was also heterogeneity of findings across different study centers and countries [13]. In the present study, fruit consumption ≥3 times a week appeared to be a protective factor against persistent asthma, with an OR of 0.85 (95% CI 0.48-1.50), although the result was not statistically significant.…”
Section: Discussioncontrasting
confidence: 77%
“…Recently, Ellwood, et al [4,13] reported the global results of the ISAAC study (Phase III) on the association between food consumption in the last 12 months and atopic diseases such as asthma, rhinoconjuctivitis and eczema. Fruit intake ≥3 times per week was found to be a protective factor against severe asthma in both adolescents and children, with OR (95% CI) of 0.89 (0.82-0.97 and 0.86 (0.76-0.97), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women with uncontrolled asthma had higher intakes of SFA, MUFA, total carbohydrate, sugar and fibre, such that for each additional 40 g of carbohydrate intake, equivalent to 2·5 slices of white bread per day, the odds of uncontrolled asthma increased by 40 %, while for each additional 10 g increase in sugar intake, equivalent to two teaspoons of added sugar per day, the odds of uncontrolled asthma increased by 10 %. Our findings are important as human epidemiological studies have shown in asthmatic adults that higher fat and lower fibre intakes were associated with worse airway inflammation and lung function (9) and fast-food consumption ≥3 times per week was associated with increased risk of severe asthma in children and adolescents (24) . Most recently, in a meta-analysis of observational studies, total intake of fruit and vegetables was inversely associated with risk of asthma in adults (six studies: RR = 0·64; 95 % CI 0·41, 1·01) and children (two studies: RR = 0·57; 95 % CI 0·42, 0·77), but higher consumption of fruit and vegetables during pregnancy was not associated with risk of asthma in offspring (25) .…”
Section: Discussionmentioning
confidence: 57%